Dissection and Re-entry Techniques for Chronic Total Occlusion Percutaneous Coronary Intervention - Reza Masoomi; Marouane Boukhris; Silvia Moscardelli; Lorenzo Azzalini (Interventional Cardiology: Reviews, Research, Resources)
Despite early stagnation in success rates for percutaneous coronary intervention for chronic total occlusion with the traditional antegrade wiring approach, the introduction of dissection/re-entry techniques and the retrograde approach opened new avenues for operators to tackle more complex occlusions. Dissection/re-entry techniques (both antegrade and retrograde) are commonly used in angiographic scenarios characterised by long, tortuous and calcified occlusions, as well as in those with proximal cap ambiguity. Familiarity and comfort using the extraplaque space (with either an antegrade or retrograde approach) have become fundamental to achieving safe and effective recanalisation of complex chronic total occlusions. This review provides an overview of different contemporary antegrade and retrograde dissection re-entry techniques and their acute and longer-term outcomes.